The Implementation of Managerial Competence of School Principals in Improving the Quality Culture of Public High Schools in West Aceh - Umar, Ferryzal; Niswanto, Niswanto; Ismail, Ismail (Indonesian Journal of Applied and Industrial Sciences (ESA), 2025)
The managerial competence of school principals plays a key role in creating and maintaining a quality culture in schools. In education, a quality culture is the collective commitment of all school members to consistently achieve and maintain high standards. This study aims to describe the implementation of school principals' managerial competence in improving school quality. A qualitative approach with a descriptive method was used. The subjects were 5 principals and 20 teachers from public high schools in West Aceh. Data collection techniques included interviews and observations. The study concluded that: 1) Principals involve teachers in school planning and management, fostering an organizational culture through collaboration, good communication, and teacher empowerment. Resources are managed transparently and accountably. Regular supervision ensures effective program implementation. 2) The quality culture is reflected in the principal's role as a manager, creating a conducive learning environment with adequate facilities and enforcing discipline to ensure a high-quality learning atmosphere. 3) Obstacles include limited resources, lack of student interest, maintaining teacher and parent cooperation, time constraints, and low school motivation in implementing a quality culture.